2018
DOI: 10.1146/annurev-clinpsy-032816-045054
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Telomeres, and Psychopathology: Toward a Deeper Understanding of a Triad of Early Aging

Abstract: Telomeres play an important part in aging and show relationships to lifetime adversity, particularly childhood adversity. Meta-analyses demonstrate reliable associations between psychopathology (primarily depression) and shorter telomere length, but the nature of this relationship has not been fully understood. Here, we review and evaluate the evidence for impaired telomere biology as a consequence of psychopathology or as a contributing factor, and the important mediating roles of chronic psychological stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 147 publications
2
84
1
2
Order By: Relevance
“…Literature to-date suggests that factors associated with shorter TL such as heightened cortisol, decreased mitochondrial number, immuno-inflammatory activation, and oxidative stress can dynamically influence neuron survival, synapse formation, the generation of action potentials, and region-specific differences in brain volume (Epel & Prather, 2018;King et al, 2014;Mamdani et al, 2015;Mottahedin et al, 2017;Nilsonne, Tamm, Månsson, Åkerstedt, & Lekander, 2015;Powell et al, 2018;Wang & Michaelis, 2010;Warren et al, 2018). Literature to-date suggests that factors associated with shorter TL such as heightened cortisol, decreased mitochondrial number, immuno-inflammatory activation, and oxidative stress can dynamically influence neuron survival, synapse formation, the generation of action potentials, and region-specific differences in brain volume (Epel & Prather, 2018;King et al, 2014;Mamdani et al, 2015;Mottahedin et al, 2017;Nilsonne, Tamm, Månsson, Åkerstedt, & Lekander, 2015;Powell et al, 2018;Wang & Michaelis, 2010;Warren et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature to-date suggests that factors associated with shorter TL such as heightened cortisol, decreased mitochondrial number, immuno-inflammatory activation, and oxidative stress can dynamically influence neuron survival, synapse formation, the generation of action potentials, and region-specific differences in brain volume (Epel & Prather, 2018;King et al, 2014;Mamdani et al, 2015;Mottahedin et al, 2017;Nilsonne, Tamm, Månsson, Åkerstedt, & Lekander, 2015;Powell et al, 2018;Wang & Michaelis, 2010;Warren et al, 2018). Literature to-date suggests that factors associated with shorter TL such as heightened cortisol, decreased mitochondrial number, immuno-inflammatory activation, and oxidative stress can dynamically influence neuron survival, synapse formation, the generation of action potentials, and region-specific differences in brain volume (Epel & Prather, 2018;King et al, 2014;Mamdani et al, 2015;Mottahedin et al, 2017;Nilsonne, Tamm, Månsson, Åkerstedt, & Lekander, 2015;Powell et al, 2018;Wang & Michaelis, 2010;Warren et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although the reasons behind functional changes to the normal brain as we age are likely complex, there is relevant research linking TL with the health and function of neurons. Literature to-date suggests that factors associated with shorter TL such as heightened cortisol, decreased mitochondrial number, immuno-inflammatory activation, and oxidative stress can dynamically influence neuron survival, synapse formation, the generation of action potentials, and region-specific differences in brain volume (Epel & Prather, 2018;King et al, 2014;Mamdani et al, 2015;Mottahedin et al, 2017;Nilsonne, Tamm, Månsson, Åkerstedt, & Lekander, 2015;Powell et al, 2018;Wang & Michaelis, 2010;Warren et al, 2018). Consequently, environmental stressors may cumulatively impact upon TL, the health of neurons, and the functional reorganization of the brain as we age.…”
mentioning
confidence: 99%
“…We are also interested in expression profiles of genes involved in telomere length maintenance (TM) via activation of telomerase. Mean telomere length in human leukocytes is negatively correlated with lifespan and BMI [42,43] and it associates with heart diseases, type 2 diabetes, cancer [44][45][46], lifestyle factors [47], diet [48] and psychological stress [49]. TM-genes are more active in type 2 transcriptomes, which suggests that they stronger counteracts telomere shortening in younger (and…”
Section: A Modular Map Of Gene Activationmentioning
confidence: 99%
“…In the context of psychiatry, meta-analyses reveal that, in general, psychiatric disorder patients exhibit shorter leukocyte telomere lengths relative to unaffected individuals of equivalent ages, which could contribute to the increased burden of age-related disease (21)(22)(23)(24). In addition to shorter telomere lengths, psychiatric disorder patients frequently exhibit neurological differences such as smaller hippocampi (25)(26)(27), and some studies have suggested a relationship between shortened telomere length and psychiatric disorder neuropathology (28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%